EVALUASI KINERJA PELAKSANAAN PROGRAM JAMINAN KESEHATAN NASIONAL TAHUN 2015 PADA KABUPATEN KUTAI BARAT - Catur Kumala Dewi., Putra Mahardhika, Elfreda Aplonia Lau, (EKONOMIA, 2017)
Performance Evaluation of implementation national health assurance program needed to know the weakness/lack of the implementation, so the service can be improve after improvement the weakness/the lack. Based of Badan Pengawasan Keuangan and Pembangunan  audit result, founded some of problems about implementation national health assurance program at city/regency in East Kalimantan. Some problems that founded are facilities, tools and health equipments at local government clinic and hospital didn’t appropriate with standart, health human resources at local government clinic and hospital didn’t appropriate with standart, and stock-out medicine occur at local government clinic.This research have a purpose to know the performance of implementation national health assurance program 2015 at Kutai Barat Regency appropriate with stipulations/regulations that obtains, that is health ministry regulation number 30 year 2014, number 56 year 2014, number 58 year 2014, number 75 year 2014, and number 36 year 2015.The data that used to Performance Evaluation of implementation national health assurance program 2015 at Kutai Barat Regency are obtained from helath official, BPJS, Hospital, and local government clinic that be sample. Analisis tool that used in this research is performance assessment tabulation of national health assurance program as exist in technical instruction of national health assurance performace audit 2015.The result from this research is scor achievement  performance of implementation national health assurance program 2015 at Kutai Barat Regency is 68,59 with category successful enough. Because the performance achievement score under 80, so can called the implementation national health assurance program not achieve successful appropriate with stipulations/regulations that obtains, that is health ministry regulation number 30 year 2014, number 56 year 2014, number 58 year 2014, number 75 year 2014, and number 36 year 2015.The conclusion of this research is the implementation of national health assurance program not achieve successful appropriate with stipulations/regulations that obtains, that is health ministry regulation number 30 year 2014, number 56 year 2014, number 58 year 2014, number 75 year 2014, and number 36 year 2015.